FRI0473 What Proportion of Patients with PSA Fail To Achieve Mda Based on Patient Reported Outcomes? An Analysis from A Prospective, Observational Registry. (15th July 2016) - Rahman, P.; Avina-Zubieta, A.; Arendse, R.; Bensen, W.; Baer, P.; Kelsall, J.; Starr, M.; Stewart, J.; Sholter, D.; Zummer, M.; Picard, L.; Rampakakis, E.; et al.
Abstract : Background: Recent treat-to-target guidelines in PsA recommend that minimal disease activity (MDA) is achieved as early as possible. Patient reported outcomes (PROs) have been criticized for not accurately assessing PsA disease activity as they may reflect aspects not directly related to PsA such as fibromyalgia, depression or other comorbidities. Objectives: The aim of this analysis was to assess the proportion of patients failing to achieve MDA based on PROs in a real-world, routine clinical care setting in Canada. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for rheumatoid arthritis, ankylosing spondylitis, or PsA with infliximab (IFX) or golimumab (GLM). Eligible participants for this analysis included those with PsA treated with IFX who were enrolled since 2005 or with GLM enrolled since 2010 and with available MDA information at baseline, 6 months, and/or 12 months. MDA was defined as the fulfillment of ≥5 of the following criteria: TJC28≤1, SJC28≤1, PASI≤1, pain (VAS)≤15 mm, PtGA (VAS)≤20 mm, HAQ≤0.5, tender entheseal points ≤1. Near MDA was defined as fulfillment of 4 criteria. Results: A total of 196 PsA patients (51.4% male) were included with a mean (SD) age of 49.8 (11.1) years and disease duration since diagnosis of 5.4 (6.3) years. The majority (62.2%) received concomitant DMARD therapy. The proportion of patients with MDA at baseline, 6 months and 12 months was 11.7%, 43.5%, and 44.8%, respectively. Overall, achievement of each individual MDA criterion was: TJC28: 43.0% of cases; SJC28: 51.3%; PASI 68.7%; pain: 27.7%; PtGA: 34.9%; HAQ: 36.8%; entheseal points: 79.4%. Among the 309 instances of non-MDA, 51 (16.5%) were near MDA cases. The most common reason for non-MDA in near MDA cases was patient-reported pain (82.4%) followed by PtGA (68.6%), and HAQ-DI (60.8%). Assuming that these criteria were met (i.e., not included in the MDA formula), the total number of MDA instances would increase from 29.6% to 36.7% (HAQ), 37.6% (PtGA), and to 39.2% (pain). Conclusions: The results of the current analysis have shown that, similar to prior analyses in RA, the most common limiting factors in achieving MDA in PsA are PROs, including PtGA, pain, and HAQ-DI, accounting for as many as 82.4% of near MDA cases. Further analyses are required to identify the determinants of the differences in PROs and clinical outcomes. Disclosure of Interest: P. Rahman: None declared, A. Avina-Zubieta: None declared, R. Arendse: None declared, W. Bensen: None declared, P. Baer: None declared, J. Kelsall: None declared, M. Starr: None declared, J. Stewart: None declared, D. Sholter: None declared, M. Zummer: None declared, L. Picard: None declared, E. Rampakakis: None declared, E. Psaradellis: None declared, K. Masolova Employee of: Janssen, A. Lehman Employee of: Janssen, F. Nantel Employee of: Janssen, C. Tkaczyk Employee of: Janssen, B. Osborne Employee of: Janssen